SARS-CoV-2 seroprevalence and neutralizing activity in donor and patient blood - Dianna L. Ng (Nature Portfolio, 2020)
Highly accurate antibody tests for SARS-CoV-2 are needed for surveillance in low-prevalence populations. Here, the authors find seroprevalence of less than 1% in two San Francisco Bay Area populations at the beginning of April, and that seroreactivity is generally predictive of in vitro neutralising activity.